Perkiraan Greenhouse Gases (GHGs) Sampah Berbasis 4R (Reduce, Reuse, Reclycle, Replace) Lingkungan Kampus - Irawan, Andik; Adi Tyagita, Dicky; Triadji Nugroho, Wendy; Wahyudiono, Arif; Ramadan, Sahrul; Alvian, M Syahrul (P3M Politeknik Negeri Jember, 2025)
Campus waste management based on the principles of Reduce, Reuse, Recycle, Replace (4R) is a strategic approach to support carbon-neutral targets through the reduction of Greenhouse Gases (GHG). This study aims to estimate the GHG emission reduction potential of 4R activities in the academic community of Politeknik Negeri Jember. Questionnaire survey data from 309 respondents, divided by study program Automotive Engine, Renewable Energy, and Mechatronics Engineering, were categorised into 4R activities. The results showed that the participation contribution in the Recycle category was 82.5% and Replace 78.5%, Reduce 77.75% and Reuse 74%. Emission reduction estimation was conducted using the Life Cycle Assessment (LCA) approach based on IPCC emission factors, which takes into account the composition of organic waste, plastic, paper and residue. The LCA analysis showed that implementing the 4R has the potential to reduce emissions by 1.2tons of CO₂-eq per month, with the largest contribution from the activities of Reduce 360kg, Reuse 300kg, Recycle 300kg, and Replace 240kg. The findings indicate that participatory-based interventions and integration of the campus environmental curriculum play an important role in building a low-carbon ecosystem.